Utilizing the Asia-Africa Conference Museum as a Historical Learning Resource: A Case Study at a Bandung Senior High School - Aulia Gita Fitriani Nur Azizah (Indonesian Journal of History Education, 2025)
This qualitative case study investigates the utilization of the Asia-Africa Conference Museum (Museum KAA) as a learning resource for teaching democratic liberal history to twelfth-grade social studies students in Bandung, Indonesia. Through observations, interviews, and document analysis, the research explores how teachers integrate this local heritage site into their pedagogy. Findings indicate that while educators recognize the museum's significant potential for fostering contextual and authentic historical understanding, its direct use remains limited due to structural constraints such as time restrictions and scheduling conflicts. Consequently, teachers often resort to digital adaptations, including videos and virtual materials, as alternative resources. The study highlights the tension between the ideal of place-based learning and the practical realities of the formal curriculum. It contributes to discussions on contextual history pedagogy and the innovative use of local historical sites to enhance historical literacy and student engagement within Indonesia’s educational landscape.